The Analogy Between Atemporal and Intertemporal Theories of Resource Allocation - Malinvaud, E. (Review of Economic Studies, 1961)
The Analogy Between Atemporal and Intertemporal Theories of Resource Allocation Get access E. Malinvaud E. Malinvaud Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 3, June 1961, Pages 143–160, https://doi.org/10.2307/2295944 Published: 01 June 1961